2020
DOI: 10.1177/2473011419898265
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation With a Novel Cadaveric Model Using Supination and Pronation Testing of a Lisfranc Ligament Injury

Abstract: Background: Lisfranc joint injuries can be due to direct or indirect trauma and while the precise mechanisms are unknown, twisting or axial force through the foot is a suspected contributor. Cadaveric models are a useful way to evaluate injury patterns and models of fixation, but a frequent limitation is the amount of joint displacement after injury. The purpose of this study was to test a cadaveric model that includes axial load, foot plantarflexion and pronation-supination motion, which could re-create bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…We did not expect big angular changes in our results, as it has been seen in other midfoot cadaveric studies that when ligament damage is introduced, only millimetric changes are observed. 18 In summary, our study shows that in a novel cadaveric model where axial load and pronation of the foot are applied, progressive damage of the medial column translates into significant pronation on the first ray. The naviculocuneiform joint ligament damage is the most significant one responsible for instability of the first ray, considering pronation and valgus deviation.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…We did not expect big angular changes in our results, as it has been seen in other midfoot cadaveric studies that when ligament damage is introduced, only millimetric changes are observed. 18 In summary, our study shows that in a novel cadaveric model where axial load and pronation of the foot are applied, progressive damage of the medial column translates into significant pronation on the first ray. The naviculocuneiform joint ligament damage is the most significant one responsible for instability of the first ray, considering pronation and valgus deviation.…”
Section: Discussionmentioning
confidence: 65%
“…It is highly interesting that intercuneiform damage did not produce any significant change in alignment of the analyzed segments, as one could predict from Lisfranc damage literature that C1C2 and C1M2 damage were the most important midfoot ligaments connecting the forefoot to the midfoot. 18 Having said this, we were not interested in generating a midfoot collapse, and it can be possible that a complete plantar damage to the C1C2 and C1M2 ligaments with higher axial load could have shown alignment changes. To be noted too is the small effect damage over C1M1 generated on segment alignment, as it produced small supinating changes in the frontal plane and small variable changes in the axial plane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The specimens were fixed to the E10000 Instron ElectroPuls Materials Testing Machine (Instron, Norwood, MA). The specimen mounting specifications and testing methods are well described in a sister study (Wagner et al’s Lisfranc model study 17 ). Relative positions of the screw heads were analyzed using SolidWorks 2017 (Dassault Systems, SolidWorks Corp, Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%